PENGARUH FINANCIAL DISTRESS DAN KINERJA KEUANGAN TERHADAP MANAJEMEN LABA YANG DIMODERASI GOOD CORPORATE GOVERNANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020 - Istimonah Dewi; Rokhmawati Andewi; Haryetti Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to determine the effect of financial distress and financialperformance on earnings management with good corporate governance as a moderatingvariable. This research was conducted on manufacturing companies listed on theIndonesia Stock Exchange (IDX) in 2016 – 2020. The population used weremanufacturing companies listed on the Indonesian stock exchange in 2016-2020, whichwere 144 companies. The sampling method in this study used purposive sampling so thatthe sample amounted to 25 companies. Data analysis used multiple linear regression. Theresults of the study explain that financial distress and good corporate governance haveno significant effect, while return on assets has a significant effect on earningsmanagement. Meanwhile, good corporate governance is able to moderate financialdistress and return on assets on earnings management. Keywords: Financial Distress, Return On Assets, Good Corporate Governance andEarnings Management